Comparisons of two Triassic conchostracan associations from Morocco and Colombia - Gallego, Oscar Florencio (2019)
We present a preliminar revision of two “conchostracan” assemblages from the Late? Triassic of Gondwana (Colombia and Morocco). The material came from the Timezgadiwine Formation in Irohalene locality at the Argana Valley of Morocco (Africa) and the Bocas Formation at the locality north from Bucaramanga municipality, Santander department, Colombia (South America). This preliminary study is based on the revision of the stereomicroscopic photographs and SEM images from specimens that bring enough diagnostic characters to identify some Triassic species previously reported for other Triassic sequences from the northern hemisphere (North America and Europe). In the fossiliferous levels from Morocco, we identified the presence of the following species: Laxitextella laxitexta Sandberger, 1871 (early to middle Carnian), Laxitextella multireticulata Reible, 1962 (late Ladinian–early Carnian), ?Laxitextella sp., ?Howellisaura princetonensis Bock, 1953 (early to middle Carnian), ?Euestheria minuta von Zieten, 1833 (early Carnian), Euestheria spp. and ?Gregorisuella sp. In the “conchostracan” levels from Colombia we identified the presence of ?Laxitextella multireticulata Reible, 1962 (late Ladinian–early Carnian), Shipingia hebaozhaiensis Shen, 1976 (mid Norian), Euestheria ?buravasi Kobayashi, 1975 (early Norian) and Wannerestheria sp. “Conchostracan” assemblages bring some palaeontological and chronological data that allow us to estimate a Triassic age for the fossiliferous levels in both Colombia (probably Carnian–Norian) and Morocco (probably Carnian) Gondwana levels. These preliminary results provide basal information and contribute to determine the age in both geological units, and to define the taxonomical composition and the precise age of these “conchostracan” assemblages from the northern of Gondwana.